Development and functional characterization of melissa essential oil fortified k-carrageenan-based active packaging films - Saurabh Bhatia; Muhammad Jawad; Ahmed Al-Harrasi; Yasir Abbas Shah; Talha Shireen Khan; Esra Koca; Levent Yurdaer Aydemir; Dinu Thomas Thekkuden; Faisal Imam; Naif Al-Harbi (Journal of Agriculture and Food Research)
The study examined the use of Melissa essential oil (MEO) in kappa carrageenan (KC) based films as a form of active packaging for potential applications in food packaging. Concentrations of MEO used were 0.1 %, 0.5 %, 1 %, and 1.5 % (v/v) to observe changes in the biopolymer characteristics. The films were evaluated for their appearance, color, antioxidant properties, and mechanical characteristics, including tensile strength (TS) and elongation at break (EAB). The findings indicate that the increase in MEO concentration resulted in a considerable decrease in the TS and moisture content of the films. In addition, an increase in EAB and water vapor permeability (WVP) was observed due to the increase in MEO concentration. The results of color analysis show that higher MEO levels made the films opaque with increasing yellowness (b∗). Moreover, antioxidant assays revealed that increasing the concentration of MEO significantly improved the films' scavenging activity against free radicals (DPPH) and cationic radicals (ABTS+). Additionally, characterization techniques such as FTIR, XRD, SEM, and thermal assessments (TGA, DSC and DTG) were also performed. Microstructural analysis revealed that a higher MEO concentration led to a few particles in the film structure. Overall, the results indicate a relatively consistent microstructure. The thermal analysis revealed that the increase in MEO concentration leads to a noticeable improvement in the film's thermal stability.